English for Specific Purposes: Tailoring English language instruction for history majors - Asya S. Akopova (Training, Language and Culture, 2023)
While English for Specific Purposes (ESP) has demonstrated efficacy in multiple professional and academic fields, its application in humanities, particularly history, remains underexplored. This study addresses this gap by examining the effectiveness of a tailored ESP approach in enhancing English language proficiency among history students. The overriding aim of this research is to evaluate the potential benefits of integrating an ESP approach within history education, focusing on the specific linguistic needs and characteristics inherent in historical discourse, archaic language, and academic writing. The study poses a research question of whether a tailored ESP approach, designed around the linguistic demands of historical discourse, archaic language, and academic writing skills, can result in a significant improvement in these skills among history students. This quasi-experimental study involved two groups: a control group receiving a traditional English language course and an experimental group receiving an ESP-oriented course focusing on historical discourse, archaic language, and academic writing. Participants were subjected to pre- and post-intervention tests to measure the efficacy of the ESP approach. The experimental group demonstrated statistically significant improvements in all three areas compared to the control group. The observed benefits were not only statistically significant but also educationally meaningful. The findings point to the efficacy of the ESP approach in history education, suggesting a potential avenue for innovation in English language instruction. They also expose the need to align language instruction with the specific linguistic characteristics of the learners’ field of study, offering supporting observations for further advancements in ESP pedagogy. Future research should explore the long-term effects of the ESP-oriented approach on history students’ language proficiency and academic performance, ideally through a longitudinal study. Investigating the adaptability of tailored ESP programmes in other humanities disciplines beyond history could also yield data regarding their efficiency in diverse academic contexts.